The Social Cartography of Chapiquiña: Revindicating Indigenous Territorial Rights in the Highlands of Arica, Chile - Joselin Leal Landeros; Alan Rodríguez Valdivia (Íconos)
This study attempts to demonstrate how methods of social cartography can serve as a political tool for the re-vindication of indigenous rights. This study employed methods of social cartography to map indigenous territorial knowledge in the indigenous community of Chapiquiña in northern Chile as a process of re-appropriation of ancestral territory. Methods of social cartography serve to make visible mental “geo-graphies” which are invisible to the Chilean state. This process led us to infer the hypothesis that the process of rural-urban migration from these Aymara communities to the city of Arica is not a process of indigenous de-territorialization. Instead we argue that these processes represent the transformation and construction of contemporary rural-urban Aymara territory.